Development of Hepatocellular Carcinoma in Patients Aged 75–84 Years With Chronic Hepatitis C Treated With Direct-Acting Antivirals. (25th June 2020) - Ogawa, Eiichi; Nomura, Hideyuki; Nakamuta, Makoto; Furusyo, Norihiro; Kajiwara, Eiji; Dohmen, Kazufumi; Kawano, Akira; Ooho, Aritsune; Azuma, Koichi; Takahashi, Kazuhiro; Satoh, Takeaki; Koyanagi, Toshimasa; et al.
Abstract: Background: Direct-acting antiviral (DAA) treatment has revolutionized hepatitis C virus (HCV) care. We aimed to evaluate the risk for the development of hepatocellular carcinoma (HCC) in patients aged 75–84 years with chronic hepatitis C after HCV elimination. Methods: This multicenter cohort study included 2405 consecutive patients with chronic hepatitis C without a history of HCC who achieved HCV elimination by DAAs. Patients in whom HCC developed within 1 year of DAA initiation were excluded. Propensity score matching analysis was used to evaluate differences in HCC risk between patients aged 75–84 versus 60–74 years. Results: The median observational period was 3.5 years. Among patients aged 75–84 years with a high Fibrosis-4 (FIB-4) index (≥3.25 at baseline), there was no significant difference in the annual incidence of HCCs between groups with an FIB-4 index ≥3.25 (2.75 per 100 person-years [PY]) versus <3.25 (2.16 per 100 PY) at 12 weeks after the end of treatment, unlike the results in those aged 60–74 years (3.61 and 1.51 per 100 PY, respectively) (adjusted hazard ratio, 2.20; P = .04). In 495 pairs matched by propensity score matching, in patients without cirrhosis, the cumulative HCC incidence was significantly higher in the 75–84-year than in the 60–74-year age group ( P = .04). Conclusions: Older patients aged 75–84 years remained at high risk for the development of HCC, even after HCV elimination and the improvement of the FIB-4 index to <3.25. Abstract : This study was performed to elucidate the risk of hepatocellular carcinoma (HCC) after elimination of hepatitis C virus in patients aged ≥75–84 years. Fibrosis biomarker improvement had little positive effect on HCC risk for patients in this age group.